2020
DOI: 10.2471/blt.20.275214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safeguarding Healthcare Workers Amidst COVID-19: A Surveillance Programme in a Teaching Hospital in Malaysia.

Abstract: DISCLAIMER This paper was submitted to the Bulletin of the World Health Organization and was posted to the COVID-19 open site, according to the protocol for public health emergencies for international concern as described in Vasee Moorthy et al. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Analysis of respondents that had COVID-19 exposure in our study showed more respondents had healthcare-related exposure compared to community-related exposure. Similar finding from a study among HCWs in COVID-19 designated facilities in Klang Valley, Malaysia also reported that the most of their respondents were having healthcare-related exposure (68.9%) [19]; also in another study in designated teaching hospital in Malaysia which reported 1,418 (24.3%) HCWs had COVID-19 exposure with 1,174 (82.8%) had healthcare-related exposure in Malaysia [22]. Healthcare-related exposure is highest in all three (3) studies in Malaysia due to more healthcare workers' time spent in the work environment as Malaysia government policy enforces strict standard operating protocol in community and travel restriction within district and states.…”
Section: Advances In Health Sciences Research Volume 44supporting
confidence: 79%
“…Analysis of respondents that had COVID-19 exposure in our study showed more respondents had healthcare-related exposure compared to community-related exposure. Similar finding from a study among HCWs in COVID-19 designated facilities in Klang Valley, Malaysia also reported that the most of their respondents were having healthcare-related exposure (68.9%) [19]; also in another study in designated teaching hospital in Malaysia which reported 1,418 (24.3%) HCWs had COVID-19 exposure with 1,174 (82.8%) had healthcare-related exposure in Malaysia [22]. Healthcare-related exposure is highest in all three (3) studies in Malaysia due to more healthcare workers' time spent in the work environment as Malaysia government policy enforces strict standard operating protocol in community and travel restriction within district and states.…”
Section: Advances In Health Sciences Research Volume 44supporting
confidence: 79%
“…XXX has a total of 1,600 beds and 22 ICU beds. More than 150 beds were designated for COVID-19 patients [ 17 ]. This study was conducted over a period of two months (April to June 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A similar study conducted by Kluytmans-van den Bergh MFQ et al [5] in Dutch hospitals reported an infection rate of 1% among HCWs. In our local settings, a study by University Malaya Medical Centre reported a prevalence of 0.3% COVID-19 infection among HCWs [6]. On March 20th, 2020, the Ministry of Health (MOH) Malaysia reported the first case of a HCW in Malaysia who was a trainee nurse at a private hospital becoming infected with COVID-19 [7].…”
Section: Introductionmentioning
confidence: 99%